Konsep Pengembangan Lembaga Pendidikan Madrasah Era Globalisasi - Wasiah (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
Madrasas as educational institutions have an important mission in preparing citizens, especially the younger generation of Muslims to play a role in the development of the people and nation in the future. Madrasas are very dynamic educational institutions. In the interaction of madrasas with globalization which develops in a sustainable manner and will indirectly have an impact on the education carried out in the madrasas themselves. Globalization not only has a positive impact on the sustainability of madrasas in Indonesia but also has a negative impact. For this reason, it is necessary to revitalize the elements of education that are owned so that they become better, so that the goals and educational processes carried out can be achieved and carried out optimally.